Soil Degradation Mapping in Sulaimani Territories, Kurdistan Region of Iraq using GIS Techniques - Abdalla, Zhino O.; Abdalkarim, Kwestan O. (Sulaimani Journal for Pure and Applied Sciences, 2021)
The phenomenon of desertification refers to the degradation of lands that cause instability in social and economic conditions. This study aims to evaluate desertification intensity in the Sulaimani area, Kurdistan Region, Northeastern Iraq. For this study, the Iranian Model of Desertification Potential Assessment (IMDPA) is adopted to evaluate the intensity based on different soil criteria, including; (i) Soil Depth, (ii) Electrical Conductivity (Ec), (iii) Texture, (iv) Gravel percentage. Three interpolation techniques (Inverse distance weighting (IDW), Kriging, and Spline) are applied to create a spatial distribution map. The results indicated that the soil depth has a significant effect, but Ec and rock fragments have less effect. The desertification map showed that 53.7% and 46.3% of the total study area are classified as low as a medium class of desertification intensity, respectively. These results have a significant role in the decision-making process for better land management.
Keywords: IMDPA; Desertification; Interpolation; Soil; Sulaimani; Iraq